PENGARUH PENILAIAN KINERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI LINGKUNGAN SMAS AL-IZZAH BATU - Prastiawan, Bagus Andi; Ernani, Ernani Hadiyati (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to determine the effect of performance appraisal and compensation on employee performance in the SMAS Al-Izzah Batu environment both simultaneously and partially. This type of research uses quantitative methods. The population of this study were Academic Teachers at SMAS Al-Izzah Batu, totalling 60 people, and the technique, and the retrieval used the Saturated Sampling technique. The data collection method involved distributing questionnaires to gather primary data. For analysis, the study applied multiple linear regression analysis, which was verified through reliability and validity assessments. Additionally, the study conducted T tests, F tests, and calculated the coefficient of determination (R2) after conducting a classical assumption tests. Data analysis was conducted using the SPSS version 26 programme. The results show that this study partially performance appraisal and compensation have a positive and significant effect on employee performance, and simultaneously employee performance has a positive and significant effect on performance appraisal and compensation.